Karakteristik dan Kontribusi Perempuan Pekerja Usaha Wisata Bahari di Kelurahan Kasawari Kecamatan Aertembaga Kota Bitung - Manueke, Renada Amelily; Dien, Christian R.; Tambani, Grace O.; Durand, Swenekhe S.; Andaki, Jardie A.; Longdong, Florence V. (AKULTURASI, 2024)
Abstract The objectives of the research are: 1) to determine the characteristics of female marine tourism business workers and 2) to determine the contribution to household income of female marine tourism business workers in Kasawari Village, Aertembaga District, Bitung City. The time required for this research, starting from consultation, pre-survey, proposal examination, fieldwork, data analysis, consultation, report writing, to comprehensive examination, is approximately 5 months from November 2023 to April 2024. The method used in this research is the survey method. The survey method is research that takes samples from a population and uses a questionnaire as the main data collection tool. Data collection was carried out on female marine tourism business workers and the contribution to household income in Kasawari Village. Data collection was carried out by means of observation, interviews and filling out questionnaires. The number of respondents taken purposively was 13 housewives. The sample was purposively selected, namely housewives who worked, both in marine tourism and beach tourism businesses. The data obtained was processed and analyzed descriptively. To calculate the contribution, a simple descriptive analysis is used, namely comparing the income of the wives of marine tourism workers to the total family income. The income data obtained was analyzed without statistical tests by calculating the amount of money earned from work carried out by women divided by total household income multiplied by one hundred percent. Based on the results of the research and discussion, it can be concluded: 1) the characteristics of female workers, in this case female marine tourism business workers, choose to work hard to support the family economy. Female marine tourism business workers mostly work in the age range of 31-40 and 41-50 because at this age female respondents working in marine tourism businesses are wiser in taking the initiative to do a job. However, education is not the main factor in working because the work carried out by respondents only requires attitudes and skills in doing the work; and 2) the contribution can be seen from the various types of work carried out by women working in marine tourism businesses, namely 55.69% of the total family income.  Key words: marine tourism; working women; income; contribution   Abstrak Tujuan penelitian, yaitu: 1) mengetahui karakteristik perempuan pekerja usaha wisata bahari dan 2) mengetahui kontribusi pendapatan rumah tangga perempuan pekerja usaha wisata bahari di Kelurahan Kasawari Kecamatan Aertembaga Kota Bitung. Waktu yang dibutuhkan dalam penelitian ini, mulai dari konsultasi, pra-survey, ujian proposal, turun lapangan, analisis data, konsultasi, penulisan laporan, sampai ujian komprehensif kurang lebih 5 bulan mulai November 2023 sampai April 2024. Metode yang digunakan dalam penelitian ini ialah metode survei. Metode survei merupakan penelitian yang mengambil sampel dari satu populasi dan menggunakan kuesioner sebagai alat pengumpul data yang pokok. Pengumpulan data dilakukan pada perempuan pekerja usaha wisata bahari dan kontribusi pendapatan rumah tangga di Kelurahan Kasawari. Pengumpulan data dilakukan dengan cara observasi, wawancara, dan pengisian kuesioner. Jumlah reponden diambil secara purposive sebanyak 13 ibu rumah tangga. Penentuan sampel secara purposive dipilih yaitu ibu rumah tangga yang bekerja, baik pada usaha wisata bahari maupun wisata pantai. Data yang diperoleh diolah dan dianalisis secara deskriptif. Guna menghitung kontribusi digunakan analisis deskritif sederhana, yaitu membandingkan pendapatan isteri pekerja wisata bahari terhadap pendapatan total keluarga. Data pendapatan yang diperoleh dianalisis tanpa uji statistik dengan menghitung jumlah uang yang diperoleh dari suatu pekerjaan yang dilakukan perempuan dibagi dengan pendapatan total rumah tangga dikali seratus persen. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan : 1) karakteristik pekerja perempuan dalam hal ini perempuan pekerja usaha wisata bahari, memilih bekerja keras untuk menopang perekonomian keluarga. Perempuan pekerja usaha wisata bahari kebanyakan bekerja pada kisaran umur 31-40 dan 41-50 karena pada umur dewasa ini responden perempuan pekerja usaha wisata bahari ini lebih bijak dalam mengambil inisiatif untuk melakukan suatu pekerjaan. Namun pendidikan tidak menjadi faktor utama dalam bekerja karena pekerjaan yang dilakukan oleh responden hanya diperlukan sikap dan keterampilan dalam melakukan pekerjaan; dan 2) kontribusi dapat dilihat dari berbagai jenis pekerjaan yang dilakukan perempuan pekerja usaha wisata bahari yaitu sebesar 55,69% dari total pendapatan keluarga. Kata kunci: wisata bahari; perempuan pekerja; pendapatan; kontribusi